Optimising capacity–coverage of a fixed WiMAX network. Issue 10 (1st July 2014) - Sharma, Satyendra; Singh, Brahmjit
Abstract : The capacity and coverage area are the two most important design considerations for the planning and optimisation of cellular networks. In this paper, we report on the field measurements of received signal strength (RSS) and available data transfer rate (DTR) at user end in a fixed WiMAX network operating at 2.62 GHz. The coverage area of the network under study covers both rural and urban sectors. Comprehensive measurements of RSS and available DTR are recorded for different settings of the base station antenna tilt and the height of customer premise equipment (CPE) antenna installed at the user premise. It is a directional antenna oriented towards the base station facilitating line of sight communication. It is interesting to observe that base station antenna down‐tilt of 2° results in almost 100% fulfilment of the coverage and capacity requirements in rural sector of the network. Up‐tilt of 1°, yields 97% fulfilment of the requirements in the entire cell area. These settings of the base station antenna tilt offers encouraging results for the optimisation of both capacity and coverage area and establishes that antenna tilt is an effective optimisation tool to achieve better utilisation of the network resources with enhanced quality of service.